Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

High incidence of estrous cycle irregularities in heterogeneous stock (HS) rats is associated with footshock-resistant cocaine intake - Elizabeth A. Sneddon; Supakorn Chonwattanagul; Kathleen Bai; Pranav H. Kurup; Sonja L. Plasil; Michelle R. Doyle; Sélène Zahedi; Sierra Simpson; Benjamin C. Sichel; Dyar N. Othman; Molly Brennan; Abraham A. Palmer; et al. (Psychopharmacology, 2026)
Rationale Hormonal fluctuations throughout the estrous cycle are hypothesized to influence drug-related behaviors. Preclinical models show that some cocaine-related behaviors are influenced by the estrous cycle. However, the extent to which the estrous cycle modulates cocaine self-administration in outbred heterogeneous stock (HS) rats is unknown. Objectives We aimed to examine the relationship between estrous phases and cocaine self-administration behavior in HS rats using an operant model of extended access to cocaine self-administration. Methods We assessed the escalation of intake, breaking point, and resistance to foot shock. Using vaginal swabbing and lavage techniques, we characterized the relationship between estrous phase and cocaine behaviors. We then comprehensively evaluated estrous cycling patterns in young adult and adult HS rats, comparing them with Wistar rats. Results Estrous phase showed no association with cocaine self-administration in HS rats. 82% of female HS rats exhibited irregular estrous cycling with variability to the phase length, even in the absence of drug exposure, a phenomenon not observed in the Wistar strain. Females with irregular cycling showed greater footshock-resistant cocaine intake. Conclusions This study provides the first evidence that most female HS rats exhibit irregular estrous cycling. In HS rats, the estrous phase per se has no major influence on cocaine self-administration, whereas cycling irregularity was associated with specific addiction-related behaviors, including footshock-resistant intake. As HS rats gain popularity in behavioral and genome-wide studies, understanding these cycle disruptions is crucial as they may reveal genetic links into cycling variability and individual differences to aspects of cocaine use.

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Microscale analysis of the fish Knightia eocaena taphonomy: Implication of a preserved microbial community - Garrett A. Rogers; Dakota R. Pittinger; Edward L. Simpson; Kurt Friehauf (Palaeobiodiversity and Palaeoenvironments, 2025)
Microbial communities are important components controlling the fidelity of fossil fish preservation. The Eocene Green River Formation lagerstätten, exceptionally preserved fossil deposits, provides an opportunity to examine the role of microbial communities and their metabolic byproducts, such as chemical precipitated in this spectacularly preserved fish deposit, famous throughout the world. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy system (EDS) examination of a well-preserved Knightia eocaena from the Eocene Green River Formation documents the presence of bacteriomorphs. Bacteriomorphs in a sample from the Fossil Butte Member of the Green River Formation consists of spherical structures, coccoid-type bacteria, fibres from two-sized populations of filamentous bacteria, probable filamentous cyanobacteria, capsule-shaped, and bacilliform bacteria, all associated with framboidal iron hydroxide. Bacteriomorphs consist of external molds composed of nanometer-scale calcium carbonate spheres. Fe-oxide framboids have an amorphous exterior and a sieve-like internal structure. The sieve-like structure consists of nanometer-scale pores, probable sites of bacterial cells with walls composed of 100-nanometer-scale spheres. Fe-oxides are consistent with bacterially mediated precipitation of pyrite followed by an oxidation event. Preserved bacteriomorphs are consistent with degradation of soft tissue, limiting the preservation of soft tissue and leaving bone and scales with no appreciable soft tissue. The microfossils are restricted to the skeleton and are not found in the surrounding rock matrix, suggesting larger microbial mats may not have been present and possibly did not have a significant impact on the preservation of this specimen.

New Approach Needed To Address Declining Forestry Research Capacity And Relevancy in the US: A Call-To-Action - Robert G. Wagner; Alexander L. Friend; Emily J. Silver; Julio Rojas; Thomas R. Fox; Terry Baker; Robert Simpson (Journal of Forestry, 2025)
Recent dramatic reductions in research funding and personnel for university and government organizations by the new federal administration will reduce forestry research capacity in the coming years. However, these cuts only highlight the long-standing decline in forestry research capacity that has been occurring over the past several decades. These reductions will continue to impair the country’s ability to meet the scale and complexity of challenges facing US forests. At some point in the future, there will be an opportunity to rebuild and reshape forestry research capacity to address these challenges. Now is the time to plan the future of forestry research. Successfully rebuilding this capacity will require national support from a broad coalition of forest management organizations. Receiving this support will require substantially increasing the relevancy of research to forest managers relative to what has occurred in recent decades. We offer several suggestions for this rebuilding effort, including: 1) developing a periodic national survey of forest managers to clearly identify the most important problems they face on the ground, 2) regularly communicating results of the survey to forest researchers, program leaders of research funding agencies, policy makers, legislators, and others responsible for allocating forest research effort and funding, and 3) building on the science delivery successes of stakeholder-driven organizations such as the forest manager / university research cooperatives around the country.

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

New computational tools and experiments reveal how geometry affects tissue growth in 3D printed scaffolds - Daniel J. VandenHeuvel; Brenna L. Devlin; Pascal R. Buenzli; Maria A. Woodruff; Matthew J. Simpson (Chemical Engineering Journal, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Abrupt changes in the physical and biological structure of endorheic upland lakes due to 8‐m lake‐level variation during the 20 th century - Judith A. Bjorndahl; Cale A.C. Gushulak; Stefano Mezzini; Gavin L. Simpson; Heather A. Haig; Peter R. Leavitt; Kerri Finlay (Limnology and Oceanography, 2022)
Climate‐induced variation in lake level can affect physicochemical properties of endorheic lakes, but its consequences for phototrophic production and regime shifts are not well understood. Here, we quantified changes in the abundance and community composition of phototrophs in Kenosee and White Bear lakes, two endorheic basins in the parkland Moose Mountain uplands of southeastern Saskatchewan, Canada, which have experienced > 8 m declines in water level since ~ 1900. We hypothesized that lower water levels and warmer temperatures should manifest as increased abundance of phytoplankton, particularly cyanobacteria, and possibly trigger a regime shift to turbid conditions due to evaporative concentration of nutrients and solutes. High‐resolution analysis of sedimentary pigments revealed an increase in total phototrophic abundance (as β‐carotene) concurrent with lake‐level decline beginning ~ 1930, but demonstrated little directional change in cyanobacteria. Instead, significant increases in obligately anaerobic purple sulfur bacteria (as okenone) occurred in both lakes during ~ 1930–1950, coeval with alterations to light environments and declines in lake level. The presence of okenone suggests that climate‐induced increases in solute concentrations may have favored the formation of novel bacterial habitats where photic and anoxic zones overlapped. Generalized additive models showed that establishment of this unique habitat was likely preceded by increased temporal variance of sulfur bacteria, but not phytoplankton or cyanobacteria, suggesting that this abrupt change to physical lake structure was unique to deep‐water environments. Such climate‐induced shifts may become more frequent in the region due to hydrological stress on lake levels due to warming temperatures across the Northern Great Plains.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Unexpected shift from phytoplankton to periphyton in eutrophic streams due to wastewater influx - Nathanael T. Bergbusch; Nicole M. Hayes; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2021)
Pollution with nitrogen (N) and phosphorous (P) impairs streams by favoring suspended algae and cyanobacteria over diatom‐rich periphyton. Recently, wastewater treatment plants have been upgraded to biological nutrient removal to eliminate both P and N (mainly NH 4 + ), although little is known of the effects of this effluent on flowing waters. Here, we used high performance liquid chromatography to quantify how the abundance and composition of phytoplankton and periphyton varied in response to both influx of effluent produced by biological nutrient removal and physico‐chemical conditions in small, turbid, P‐rich streams of the northern Great Plains. At the catchment scale, analysis with generalized additive models (GAMs) explained 40.5–62.6% of deviance in total phototroph abundance (as Chl a ) and 72.5–82.5% of deviance in community composition (as biomarker carotenoids) in both planktonic and benthic habitats when date‐ and site‐specific physico‐chemical parameters were used as predictors. In contrast, GAMs using wastewater input (as aqueous δ 15 N) as a predictor explained up to 50% of deviance in Chl a , and ~60% of deviance in community composition, in both suspended (51.6% of Chl a , 67.1% of composition) and attached communities (21.5% of Chl a , 58.8% of composition). Phytoplankton was replaced by periphyton within a 60‐km wastewater‐impacted reach due to dilution of streams by transparent effluent and addition of urban NO 3 − , although predominance of phytoplankton was re‐established after confluence with higher‐order streams. Overall, influx of effluent shifted turbid, phytoplankton‐rich streams to clear ecosystems with abundant epilithon by improving water transparency and providing NO 3 − to favor benthic diatoms and chlorophytes.

The effects of normoxic endurance exercise on erythropoietin (EPO) production and the impact of selective β1 and non-selective β1 + β2 adrenergic receptor blockade - Rod J. Azadan; Nadia H. Agha; Hawley E. Kunz; Forrest L. Baker; Preteesh L. Mylabathula; Tracy A. Ledoux; Daniel P. O’Connor; Charles R. Pedlar; Richard J. Simpson (European Journal of Applied Physiology, 2021)

The Human Element of Restoration Success: Manager Characteristics Affect Vegetation Recovery Following Invasive Tamarix Control - Anna A. Sher; Lisa Clark; Annie L. Henry; Alexander R. B. Goetz; Eduardo González; Anit Tyagi; Isabelle Simpson; Bérenger Bourgeois (Wetlands, 2020)

Bayesian Inverse Transient Analysis for Pipeline Condition Assessment: Parameter Estimation and Uncertainty Quantification - Chi Zhang; Martin F. Lambert; Jinzhe Gong; Aaron C. Zecchin; Angus R. Simpson; Mark L. Stephens (Water Resources Management, 2020)

Inbreeding depression causes reduced fecundity in Golden Retrievers - Erin T. Chu; Missy J. Simpson; Kelly Diehl; Rodney L. Page; Aaron J. Sams; Adam R. Boyko (Mammalian Genome, 2019)

Seasonality of pCO 2 in a hard‐water lake of the northern Great Plains: The legacy effects of climate and limnological conditions over 36 years - Kerri Finlay; Richard J. Vogt; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2019)
Biogeochemical processes are active year‐round in ice‐covered lakes, such that processes in one season can affect limnological conditions in subsequent seasons. However, the extent and nature of these legacy effects are poorly understood, particularly for the CO 2 content of lakes and when considering gas exchange with the atmosphere. Here, we used a unique 36‐yr dataset of weekly limnological measurements of Buffalo Pound Lake in the northern Great Plains to assess seasonal changes in CO 2 concentration and flux and determine how dependent lake pCO 2 is on limnological conditions of previous seasons. We found that the lake was a net source of CO 2 to the atmosphere (mean 18.5 ± 7.4 mol CO 2 m −2 yr −1 ), with spring potentially accounting for the majority (~ 64% ± 20%) of CO 2 efflux, assuming ice in spring was permeable to gas exchange (32.9% ± 19.8% if not). Analysis with generalized additive models (GAMs) demonstrated that current and antecedent seasonal conditions combined to explain 72.6% of deviance in spring pCO 2 , but that the strength of model predictions and the importance of antecedent conditions diminished in GAMs of summer (43.6%) and fall (23.3%) CO 2 levels. This research suggests that pCO 2 is regulated by a combination of coeval and historical environmental conditions and shows that quantification of seasonal and annual fluxes requires a mechanistic understanding of the legacy effects of preceding time intervals.

Differential stimulation and suppression of phytoplankton growth by ammonium enrichment in eutrophic hardwater lakes over 16 years - Vanessa J. Swarbrick; Gavin L. Simpson; Patricia M. Glibert; Peter R. Leavitt (Limnology and Oceanography, 2019)
Previous research suggests that fertilization of surface waters with chemically reduced nitrogen (N), including ammonium (NH 4 + ), may either enhance or suppress phytoplankton growth. To identify the factors influencing the net effect of NH 4 + , we fertilized natural phytoplankton assemblages from two eutrophic hardwater lakes with growth‐saturating concentrations of NH 4 Cl in 241 incubation experiments conducted biweekly May–August during 1996–2011. Phytoplankton biomass (as chlorophyll a ) was significantly ( p 4 + increased with abundance of diatoms, cryptophytes, and unicellular cyanobacteria, particularly when water temperatures and soluble reactive phosphorus (SRP) concentrations were low. In contrast, phytoplankton was often stimulated by NH 4 + when chlorophytes and non‐N 2 ‐fixing cyanobacteria were abundant, and temperatures and SRP concentrations were high. Progressive intensification of NH 4 + effects over 16 yr reflects changes in both spring (cooler water, increased diatoms and cryptophytes) and summer lake conditions (more chlorophytes, earlier cyanobacteria blooms), suggesting that the seasonal effects of NH 4 + will vary with future climate change and modes of N enrichment.

Changes in nutritional values induced by butachlor in juvenile diploid and triploid Clarias gariepinus - A. Karami; S. Karbalaei; M. Ebrahimi; A. Ismail; M. F. Jahromi; S. L. Simpson; P. Eghtesadi Araghi; R. P. Lim; J. B. Liang (International Journal of Environmental Science and Technology, 2018)

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Influence of fascicle length on twitch potentiation of the medial gastrocnemius across three ankle angles - Samantha L. Kuzyk; Rowan R. Smart; Carey L. Simpson; Andrey Fedorov; Jennifer M. Jakobi (European Journal of Applied Physiology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)

Duration of fascicle shortening is affected by muscle architecture and sex - C. L. Simpson; S. Arefin; R. R. Smart; B. Harwood; Jennifer M. Jakobi (European Journal of Applied Physiology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Prevalence of polypharmacy in a Scottish primary care population - R. A. Payne; A. J. Avery; M. Duerden; C. L. Saunders; C. R. Simpson; G. A. Abel (European Journal of Clinical Pharmacology, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Differential expression of Phaseolus vulgaris genes induced during the interaction with Rhizoctonia solani - M. L. Guerrero-González; M. Rodríguez-Kessler; R. Rodríguez-Guerra; M. González-Chavira; J. Simpson; F. Sanchez; J. F. Jiménez-Bremont (Plant Cell Reports, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Toward increasing avian diversity: urban wildscapes programs - Amanda L. Aurora; Thomas R. Simpson; Michael F. Small; Kelly C. Bender (Urban Ecosystems, 2009)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Characteristics of an ozone deposition module II: Sensitivity analysis - D. Simpson; J.-P. Tuovinen; L. Emberson; M. R. Ashmore (Water, Air, & Soil Pollution, 2003)

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

On the role of ?hot towers? in tropical cyclone formation - J. Simpson; J. B. Halverson; B. S. Ferrier; W. A. Petersen; R. H. Simpson; R. Blakeslee; S. L. Durden (Meteorology and Atmospheric Physics, 1998)

Agrobacterium-mediated transformation of Amaranthus hypochondriacus: light- and tissue-specific expression of a pea chlorophyll a/b-binding protein promoter - A. E. Jofre-Garfias; N. Villegas-Sepúlveda; J. L. Cabrera-Ponce; R. M. Adame-Alvarez; L. Herrera-Estrella; J. Simpson (Plant Cell Reports, 1997)

Partial purification and characterisation of an aromatic amino acid aminotransferase from mung bean (Vigna radiata L. Wilczek) - R. M. Simpson; H. M. Nonhebel; D. L. Christie (Planta, 1997)